Environmental policy planning - Egbon, P. C.; Morvaridi, Behrooz (Ibadan, Nigeria : National Centre for Economic Management and Administration, 1996)
This book examines the question of environmental policy and planning with particular reference to Nigeria. Most of the issues are examined from both theoretical and empirical perspectives.
Includes bibliographical references and index.
osc 02/09/16 ijb 20/03/2019
Loans
Keywords: Environmental policy